Ultrasound Evaluation of Bone Age in Rural Ecuadorian Children and Its Association with Nutrition (FS01-08-19). (13th June 2019) - Nicholas, Jennifer; Douglas, Katherine; Waters, William; Gallegos, Carlos Andres; Chapnick, Melissa; Habif, David; True, Sarah; Musonza, Clive; Iannotti, Lora
Abstract: Objectives: This study aimed to test use of portable ultrasound technology to determine bone age in rural Ecuadorian children and investigate its association with anthropometry and dietary intakes. Methods: Children ages 2–3 years ( n = 129) from Cotopaxi Province participated in Lulun Project II, a cohort follow-up to the Lulun Project, an RCT testing the efficacy of egg intervention in complementary feeding. Data collection, including targeted ultrasounds of the hand and wrist, was undertaken in participant households. Anthropometric measures were taken using international protocols and Z scores generated with WHO Growth Standards. Results: Mean bone age z-score (BAZ) was −1.5 (±1.2); −0.9 (±1.0) among girls and −2.0 (±1.2) among boys. Bone age z-scores were positively correlated with HAZ ( r = 0.35, P < 0.001) and negatively correlated with BMI z-scores ( r = −0.27, P = 0.002), but no association between bone age and WAZ was observed. Linear regression modeling demonstrated that HAZ (0.374 95% CI 0.174–0.574), female sex of the child (0.573 95% CI 0.214–0.932), 24-hour frequency of intake for savory snacks (0.290 95% CI 0.028–0.552), child taken to healthcare facility in previous 3 mo (−0.664, 95%CI −1.160, −0.167), ownership of pigs (−0.506, 95% CI −0.863, −0.148), and cultivation of cash crops (0.466, 95% CI 0.062, 0.870) significantly predicted BAZ. Conclusions: Bone age in young children may be feasibly collected in a low-resource setting using portable ultrasound technology. As it highly correlates with HAZ and other diet anthropometric parameters, it prove to be an important tool in the evaluation of children's nutritional status. Funding Sources: The Mathile Institute for the Advancement of Human Nutrition.